The Role of Digital Social Media Marketing on Purchase Decision Jank Jank Wings Thought Brand Equity as Mediation Variable - Tiara Saraswati, Thusy; Dita Rachmawati; Indah Datin Nadliroh; Agus Hermawan; Ludi Wishnu Wardana (Jurnal Sistim Informasi dan Teknologi, 2024)
The current research examined how brand equity and social media marketing mediated the relationship between the purchasing decision of Jank Jank Wings and the analysis of that decision. Customers of Jank Jank Wings participated in this survey. Jank Jank Wing is marketed by samples 215 of target consumers who have eaten or purchased through TikTok and Instagram media, using a purposive sample technique. Each response is processed using partial least squares (PLS). The results indicate that social media marketing influences consumer decisions. The purchasing choices of consumers are impacted by the value of the brand. Brand equity's influence on social media marketing. Moreover, empirical studies have demonstrated that customer decisions are impacted by brand equity, which functions as both an intermediary and an amplifier of the impact of social media marketing. Time constraints resulted in a limited number of returned surveys, which constitutes a drawback of the research. This study suggests that Jank Jank Wings has the potential to enhance brand recognition, perceived quality, brand association, and brand loyalty by implementing social media strategies. When making decisions throughout the purchasing process, all of these components are seen to be crucial.